Pengembangan Media Pembelajaran Berbasis Flipbook Teknik Dasar Passing-Control Dalam Permainan Sepakbola Peserta Didik Kelas XI SMA Negeri 1 Mengwi - I Putu Agus Satria Perdana Jelantik; I Made Satyawan; Ni Putu Dwi Sucita Dartini (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
The rapid development of digital technology requires the integration of innovative learning media in Physical Education, Sports, and Health (PJOK) learning. However, learning activities on soccer materials, particularly passing-control techniques, are still dominated by conventional teaching methods and printed textbooks, resulting in limited student engagement and understanding. Therefore, digital learning media that are interactive, attractive, and accessible are needed to support the learning process. This study aimed to develop a flipbook-based learning media for the basic techniques of passing-control in soccer for eleventh-grade students of SMA Negeri 1 Mengwi and to determine the validity, feasibility, and student responses toward the developed product. This study employed a Research and Development (R&D) approach using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. The subjects involved one material expert, one media expert, one PJOK practitioner, and eleventh-grade students. Product testing was conducted through a small-group trial involving 15 students and a large-group trial involving 30 students. Data were collected using validation and response questionnaires and analyzed using descriptive qualitative and quantitative techniques.The validation results showed that the developed flipbook-based learning media achieved a score of 90% from the material expert, 98.66% from the media expert, and 100% from the PJOK practitioner, all categorized as very good. Student responses in the small-group trial reached 91.46%, while the large-group trial obtained 91.43%, both classified as very good. These findings indicate that the developed media met the criteria of validity and feasibility for use in PJOK learning. The flipbook-based learning media on the basic techniques of passing-control in soccer was successfully developed through the 4D model and demonstrated very good validity and feasibility based on expert evaluations and student responses. The media can be utilized as a digital learning resource to support the teaching and learning process of PJOK, particularly in soccer learning materials.